Um pedaço do Brasil: a roda de samba como espaço de lazer - O Quintal do Divina Luz - Guilherme Velloso Alves (2010)
This study aims to describe and analyze as leisure spaces the samba circles of the city of Belo Horizonte, from understanding the context in which they are inserted and the behavior of the actors who frequent them. To this end, initially a review of the literature was done seeking to reveal the historical path traced by samba music genre and its manifestations, especially the samba circle. A brief history of samba circles of the capital of Minas Gerais was raised to enable an understanding of the transformations taken by this leisure practice and understand some of the circumstances that contributed to and / or contribute to today's samba circle have certain boundaries, and not others. The importance that has the samba circle in Belo Horizonte today began with the samba circles back in the 1980s. Since then it has been forming a circuit of samba, enabling the emergence of several artists, groups and houses of samba, stimulating the formation of a samba-consuming public and the generation of work and sociability networks surrounding this manifestation. Then, we adopted an anthropological approach which, through an ethnographic study, allowed the description and analysis of sociability networks built around the samba circles as well as the ways ownership and use of those spaces and the behavior of social actors present there. To understand the samba as a leisure concept has been adopted the turf concept proposed by Magnani. One of these turfs was examined more closely, which resulted in a more acute perception of the boundaries of a samba circle. The highlighted turf of the Quintal do Divina Luz, where Roda Viva is attended, a project that not only constitutes another offer of work for organizers, but also provides an opportunity to connect with a unique set list, consisting of samba music that are obliterated by the media, as well as own compositions from the musicians who play in the circle and other composers of the local scene. The backyard look (Quintal) that referred turf still has is used as a highlighting characteristic comparing to other houses of Samba of Belo Horizonte. However, there is a tension between the desire to maintain the traditional appearance and all benefit from the institutional image that this rustic and homey look of the backyard can bring and, on the other hand, to modernize the space in order to offer more comfort to the public, better service and proper maintenance of the turf in, which involves investments in the acoustic isolation of Quintal do Divina Luz. The ambiguity on this turf goes beyond spatial remodeling printed there, but the coexistence of professionalism and amateurism. Thus it was possible, from a closer look on one of the presentation ways of samba, the samba circle, to raise some relationship between leisure and samba, as well as generate contributions to the understanding of the conformation of this culture in contemporary times.